IMPLEMENTASI KEBIJAKAN PROGRAM PENILAIAN PERINGKAT KINERJA PERUSAHAAN DALAM PENGELOLAAN LINGKUNGAN HIDUP (PROPER) DI KOTA SEMARANG - Rizqi Fahmawati; Hartuti Purnaweni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Indonesia’s program on pollution control, evaluation, and rating (PROPER— Program Penilaian Peringkat Kinerja Perusahaan dalam Pengelolaan Lingkungan Hidup) is one of the government’s policy to monitor and protect environmental management practiced by companies and industries. Semarang city, as one of Central Java’s most strategic region, is potential for industrial and business site. This study aims to analyze the implementation of PROPER and all of the contributing factors that impact the process itself. Method used for this study is qualitative descriptive method. Process from PROPER’s implementation in this region consists of preparation, direct monitoring, and the company’s adherence evaluation on the policy. Based on the result found from this study, it is shown that company’s comprehension on the policy, adequate facilities, clear standard of procedure, organized bureaucratic structure (that has eased the monitoring process), and political elite’s support are the supporting factors of PROPER’s process. However, limitation on financial resource and lack of society’s knowledge on this policy are also impeding PROPER’s full implementation in Semarang city. The author suggests the Department of Environmental and Forestry of Central Java to recruit more human resources, establish partnerships with correlating stakeholders, prioritize on fostering companies with red ranks and below, and educate the society about PROPER’s result on assessed companies. In the end, strong commitment is necessary to have for both parties; either for the companies and industries, society, and government itself to better PROPER’s implementation into becoming more effective and efficient.